2013
DOI: 10.9790/3008-0510913
|View full text |Cite
|
Sign up to set email alerts
|

The effect of He-Ne Laser and UVC irradiation on sperm head morphology and DNA of testis for albino mice(Mus musculus)

Abstract: In vitro, He-Ne laser show a modifying response of cells to ionizing radiations. So there is a need to investigate this property in vivo.To investigate the effect of He-Ne laser (632.8nm) pre and post irradiation against the UVC (253.7nm) irradiation in vivo on the sperm morphology, and DNA of testis in Mouse. In this study Twenty adult albino male mice were divided into four groups, the first group was He-Ne laser irradiated, and the second group was UVC irradiated. The third group was pre-irradiated by He-Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…It can be concluded that, He-Ne laser irradiation by it self show a toxic effect leading to some degree of sperm head abnormalities. While He-Ne laser pre ionizing irradiation (UVC) may be resulting in adversely influncing mammalian germ cell metabolism, which lowering the frequencies of sperm head abnormalities [23]. The mechanism of the He-Ne laser induce protection appears to be a sort of adaptive response.…”
Section: Resultsmentioning
confidence: 99%
“…It can be concluded that, He-Ne laser irradiation by it self show a toxic effect leading to some degree of sperm head abnormalities. While He-Ne laser pre ionizing irradiation (UVC) may be resulting in adversely influncing mammalian germ cell metabolism, which lowering the frequencies of sperm head abnormalities [23]. The mechanism of the He-Ne laser induce protection appears to be a sort of adaptive response.…”
Section: Resultsmentioning
confidence: 99%